(untitled) (Analysis in Theory and Applications, 2025)
In this paper, we generalize the Durrmeyer-type Bernstein-Schurer operator by applying (p, q)-integers and obtain uniform convergence of the operator. Furthermore, we deal with the approximation problems in terms of the modulus of smoothness and K-functional. Finally, the operator is modified to get better estimation.